2017
DOI: 10.1016/j.epsl.2017.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Sulphide–sulphate stability and melting in subducted sediment and its role in arc mantle redox and chalcophile cycling in space and time

Abstract: The redox budget during subduction is tied to the evolution of oxygen and biogeochemical cycles on Earth's surface over time. The sulphide-sulphate couple in subducted crust has significant potential for redox and control on extraction of chalcophile metals from the arc mantle. We derive oxygen buffers for sulphide-sulphate stability ('SSO buffers') using mineral assemblages in subducted crust within the eclogite facies, and examine their disposition relative to the fO 2 in the arc mantle along various P-T tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 81 publications
3
17
0
Order By: Relevance
“…Skora et al () explained this trend in the Freymuth et al () by invoking the melting of a subducting sediment package that included both black shales and low‐Ca marine clays and terrigenous sediments, where the residual mineralogy would not favor any retention of Ce but might (depending on redox conditions) favor the retention of Mo. The work of Canil and Fellows () similarly supports the important role of Ca in determining residual slab mineralogy and determining whether Mo is retained or released. Retention of some Mo in the slab during genesis of the Old Arc therefore seems reasonable.…”
Section: Discussionmentioning
confidence: 95%
“…Skora et al () explained this trend in the Freymuth et al () by invoking the melting of a subducting sediment package that included both black shales and low‐Ca marine clays and terrigenous sediments, where the residual mineralogy would not favor any retention of Ce but might (depending on redox conditions) favor the retention of Mo. The work of Canil and Fellows () similarly supports the important role of Ca in determining residual slab mineralogy and determining whether Mo is retained or released. Retention of some Mo in the slab during genesis of the Old Arc therefore seems reasonable.…”
Section: Discussionmentioning
confidence: 95%
“…Luhr, 1990;Carroll & Webster, 1994;Scaillet et al, 1998), and consequently silicate melts were usually considered not to be an efficient agent of sulphur extraction from the slab. However, experimental works have demonstrated that the sulphur content of high pressure oxidized hydrous silicic melts is at least 10-20 times higher than at low pressures (Prouteau & Scaillet, 2013;Jégo & Dasgupta, 2014;Canil & Fellows, 2017;D'Souza & Canil, 2018;Li et al, 2019). This finding reduces the restriction that the sulphur-rich character of present-day arc volcanism bears evidence solely of a sulphur-rich hydrous fluid.…”
Section: Introductionmentioning
confidence: 97%
“…Sulphur has been shown to affect the stabilities of phases other than those S-bearing, i.e. amphibole, biotite in magmas (Scaillet & Evans, 1999;Costa et al, 2004;Prouteau & Scaillet, 2013;Canil & Fellows, 2017;D'Souza & Canil, 2018). It is thus important to assess the role of S on the stability of phases of subducted sediments in order to evaluate its potential effect on trace element patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing pressure and temperature conditions during subduction drive metamorphic reactions in the slab to produce hydrous fluids or silicate melts, which transport material into the overlying system that eventually produces the magmatic arc (e.g., Hacker, ; Manning, ; Marschall & Schumacher, ). Despite the important role sulfur may play in the redox of the slab‐arc system and trace metal cycling, a limited number of studies have focused on sulfur mobilization from the slab during subduction metamorphism (Alt, Shanks, et al, , Alt, Garrido, et al, ; Canil & Fellows, ; Crossley et al, ; Debret & Sverjensky, ; Evans & Powell, ; Evans et al, , ; Jego & Dasgupta, ; LaFlamme et al, ; Lee et al, ; Tomkins & Evans, ).…”
Section: Introductionmentioning
confidence: 99%